Ondas gravitacionales (2021)
This thesis, in a compilation way, seeks to understand and study various aspects related to the phenomenon of gravitational waves. This involves deriving and demonstrating the wave properties of space-time, studying its properties as its polarization, energy-momentum. The similarities of these waves with those treated in electromagnetism will be evident. He also understands the incidences of various undulations in the particle?s movement, showing a simplified model that reveals different behaviors between the influence on a specific particle to one with dimensions. Finally, historical events and direct or indirect ways of measuring this phenomenon will also be studied.